Odpowiedzi

Najlepsza Odpowiedź!
2010-01-31T16:53:15+01:00
(y+1)²= (y+1)(y+1)=y² +2y +1
(3+2x)²=9+12x+4x²
c) (x²+1)²=x⁸ +1
d).(2a+5b)²=4a² +20ab +25b²
e) (3xy+1)²=9x²y² + 6xy + 1
f) (√3+1)²= 4 +2√3
g)(1+√2)²=3 +2√2
h) (√3+√12)²=3 +√36 + √36 + 12 = 27
1 5 1
2010-01-31T16:58:17+01:00
A) (y+1)²= y²+2y+1
b) (3+2x)²= 9+ 12x +4x²
c) (x²+1)²= x⁴+2x²+1
d) (2a+5b)²= 4a²+20ab+ 25b²
e) (3xy+1)²= 9x²y² +3xy +1
f) (√3+1)²= 3+2√3+1= 4+2√3
g) (1+√2)²= 1 + 2√2 + 2 = 3+ 2√2
h) (√3+√12)²= 3+2√3√12 + 12 = 15 + 2√36 = 15+2*6 = 15+12= 27
1 4 1